Profit reinvestment: Main motives supporting financial decisions - Pavla Pokorná; Jarmila Šebestová (e-Finanse: Financial Internet Quarterly, 2019)
Reinvestment decisions are based on basic the economic literacy of entrepreneurs because they do not want to affect future liquidity or development activities. The main goal of the article is to suggest a simple decision tree model to describe profit reinvestments in a general way based on results of a primary pilot study (128 interviews), where reinvestment behaviour is affected by specific factors like risk taking, competitive advantage or business experience. After that a decisionmaking tree is suggested to explain the process of reinvestment as determined by the manager.
Keywords: L26; M21; G31; 330; reinvestment; profit; motivation to reinvest